Impact of haemostatic sealant versus electrocoagulation on ovarian reserve after laparoscopic ovarian cystectomy of ovarian endometriomas: a randomised controlled trial. (23rd May 2019) - Chung, JPW; Law, TSM; Chung, CHS; Mak, JSM; Sahota, DS; Li, TC
Abstract : Objective: To evaluate the effect of haemostatic sealant compared with bipolar coagulation on ovarian reserve after laparoscopic cystectomy for ovarian endometriomas. Design: Patient‐blinded, randomised controlled trial. Setting: University‐affiliated tertiary hospital. Population: Women aged 18–40 years with 3–8 cm unilateral or bilateral endometriomas. Methods: Ninety‐four patients were randomised to receive haemostasis by the application of haemostatic sealant ( n = 47) or standard care ( n = 47). Main outcome measures: Primary outcome was the effect on the antral follicular count 3 months after the operation as it captures the effect on the ovary subjected to treatment. Secondary outcomes included the change in anti‐Mullerian hormone, follicular‐stimulating hormone and peri‐operative outcomes including haemostasis, complications, pain, and satisfaction scores. Results: A total of 94 patients aged 32.36 ± 4.92 years underwent laparoscopic cystectomy for ovarian endometriomas. The average diameter of the endometrioma was 4.21 ± 1.38 cm. The increase in antral follicle count of the affected ovaries at 3 months in the intervention group (+2.36 ± 0.37) was significantly ( P = 0.013) higher than that in the control group (+1.08 ± 0.36). Repeated measures analysis of variance revealed significant effect with time ( P < 0.001) and of interaction of group × time ( P = 0.029) for affected ovary antral follicle count. No significant difference was noted between the two groups with regard to follicular‐stimulating hormone, anti‐Mullerian hormone, and other secondary outcomes. Conclusions: Applying haemostatic sealant after laparoscopic cystectomy of ovarian endometriomas produced a greater increase in antral follicle count 3 months after surgery compared with the control group. Tweetable abstract: RCT: Haemostatic sealant in laparoscopic cystectomy of endometriomas increase in the antral follicle count after surgery. Tweetable abstract: RCT: Haemostatic sealant in laparoscopic cystectomy of endometriomas increase in the antral follicle count after surgery.